Reasons for Not Seeking Hepatitis C Treatment among People Who Inject Drugs. (18th November 2020) - Morris, Leith; Selvey, Linda; Williams, Owain; Gilks, Charles; Smirnov, Andrew
Abstract: Background: Despite increases in treatment uptake for hepatitis C viral infection (HCV) in Australia since the introduction of direct acting antiviral (DAA) therapy, a large proportion of HCV-infected people who inject drugs (PWID) have not sought treatment. Purpose/Objectives: To examine predictors of treatment uptake and reasons for not seeking treatment among PWID. Methods: PWID ( n = 404) recruited through five needle and syringe programs in South East Queensland were interviewed about HCV testing, status and treatment, recent injecting drug use, mental health and reasons for not taking up treatment. Predictors of treatment uptake were examined using unadjusted and adjusted logistic regression analyses. Proportions were calculated for participants reporting each reason for not taking up treatment. Results: We recruited 404 PWID. Of those tested for HCV (94%), 55% were HCV antibody positive and 31% with active infection. Approximately 36% of eligible participants had begun or completed DAA treatment. In adjusted analyses, injecting drugs three or more times per day was associated with not taking up HCV treatment ( p = 0.005). Common reasons for not seeking treatment ("applied a lot") included experiencing no HCV-related symptoms (25%), HCV treatment not being a priority (23%), fear of treatment side effects (18%), and no knowledge of DAA treatments (15%). Conclusions/Importance: HCV education efforts for PWID should target misperceptions and lack of awareness of DAA therapy, and highlight the likely benefits of treatment even when asymptomatic. The use of peer workers and increased investment in integrated treatment facilities will likely aid treatment uptake.